Rhinogenic contact point headache in pediatric age group: a review - Swain, Santosh Kumar; Baliarsingh, Prasenjit (International Journal of Contemporary Pediatrics, 2021)
Headache is a common clinical entity of pediatric patients in routine clinical practice. Anatomical variation in the nasal cavity may result in headaches due to contact of the opposing mucosal surfaces, called rhinogenic contact point headache (RCPH). RCPH has recently begun to be of interest among clinicians and is accepted as a cause of headache by international headache society classification. The pressure of the two opposing mucosal surfaces in the nasal cavity without any evidence of inflammation can be an etiology for headache or facial pain. Anatomical variations in the nasal cavity like deviated nasal septum (DNS), spur, concha bullosa, hypertrophied inferior turbinate, medialized middle turbinate, and septal bullosa are important causes for contact point headache. RCPH is often misdiagnosed by clinicians during the assessment of headaches in pediatric patients and is sometimes considered a headache of unknown etiology. Endoscopic examination of the nasal cavity and computed tomography (CT) scans are important tools for the diagnosis of anatomical variations in the nasal cavity causing RCPH. Endoscopic resection of the contact point in the nasal cavity is the treatment of choice. There is not much literature for RCPH in pediatric patients, indicating that these clinical entities are neglected. This review article discusses the details of the epidemiology, etiopathology, clinical manifestations, diagnosis, treatment of the RCPH in pediatric patients.